2017
DOI: 10.1177/1740774517717722
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians’ attitudes and beliefs about cancer clinical trials

Abstract: Background/Aims Cancer clinical trials give patients access to state-of-the art treatments and facilitate the translation of findings into mainstream clinical care. However, patients from racial and ethnic minority groups remain underrepresented in clinical trials. Primary care physicians are a trusted source of information for patients, yet their role in decision-making about cancer treatment and referrals to trial participation has received little attention. The aim of this study was to determine physicians’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Apart from the factors discussed above, previous studies found that propaganda and education addressing trial information could influence the patients' attitudes and perceptions toward clinical trials as well. The variation in knowledge of clinical trials held by primary care physicians and nurse practitioners could result in different efficiency in patient accrual and hence different probability of recruitment of participants 17-18. Our institution is a high-volume cancer center and the doctors and nurses in our institution are well-known of clinical trials and can adequately inform participants of well-organized education about the trial they signed in, which guarantees a high proportion of patients recruited in clinical trials from our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the factors discussed above, previous studies found that propaganda and education addressing trial information could influence the patients' attitudes and perceptions toward clinical trials as well. The variation in knowledge of clinical trials held by primary care physicians and nurse practitioners could result in different efficiency in patient accrual and hence different probability of recruitment of participants 17-18. Our institution is a high-volume cancer center and the doctors and nurses in our institution are well-known of clinical trials and can adequately inform participants of well-organized education about the trial they signed in, which guarantees a high proportion of patients recruited in clinical trials from our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Patients scored low on the knowledge reinforcing the need to further educate patients about CT. Healthcare providers need to portray information underlining the safety of trials. Our study was based on statements from HCPs and like several other studies reinforce the education of healthcare professionals on Clinical Research to boost recruitment rates (11). Another survey based study on the knowledge of CT (16) demonstrated that knowledge of participants on CT was limited especially on topics such as rationale of study, randomization and placebo and patient protection.…”
Section: Discussionmentioning
confidence: 84%
“…Current findings were in agreement with results from other studies done in other developing countries. 11,16,17,20 Although a large percentage of medical residents reported that they have taken training courses about clinical research at some point during their clinical training, only a small number of them showed basic knowledge about ethical standards related to patients' privacy and rights protection codes. More than two thirds of respondent residents showed adequate knowledge about informed consent importance and elements as well as when it is mandatory to be taken.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Similar studies from the USA, Japan, Saudi Arabia, and India showed that physicians involved in cancer clinical trials had little knowledge or experience about clinical trials, yet they had high interest and positive attitude to learn more about the roles they could play in clinical trial research. 11,16,20,23 These findings suggest the need to provide physicians, especially those planning to run future clinical trials, with the proper training involving the ethical challenges and other obstacles that they might encounter in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation